Mid- to Late-Life Body Mass Index and Dementia Risk: 38 Years of Follow-up of the Framingham Study. Issue 12 (8th April 2021) - Li, Jinlei; Joshi, Prajakta; Ang, Ting Fang Alvin; Liu, Chunyu; Auerbach, Sanford; Devine, Sherral; Au, Rhoda
Abstract: Growing evidence relates body mass index (BMI) to poorer health outcomes; however, results across studies associating BMI and dementia are conflicting. A total of 3, 632 Framingham Offspring participants aged 20 to 60 years at their second health examination (1979–1983) were included in this study, with 190 cases of incident dementia identified by 2017. Cox proportional hazards regression models were fitted to investigate the association of BMI at each of their 8 exams as a baseline for dementia risk and the associations between obesity and dementia across age groups. Spline models were fitted to investigate nonlinear associations between BMI and dementia. Each 1-unit increase in BMI at ages 40–49 years was associated with higher risk of dementia, but with lower risk after age 70 years. Obesity at ages 40–49 years was associated with higher risk of dementia. Overall, the relationship between BMI and dementia risk was heterogeneous across the adult age range. Monitoring BMI at different ages might mediate risk for dementia across an individual's lifetime.